Encefalopatia necrotizante aguda: paciente com evolução recidivante e letal Acute necrotizing encephalopathy: patient with a relapsing and lethal evolution - Erasmo B. Casella; Victor Nudelman; Marcelo M. Felix; Edson Amaro Jr.; Benjamin Handfas; João Radvany; Adalberto Stape; Eduardo Troster (Arquivos de Neuro-Psiquiatria)
A encefalopatia necrotizante aguda foi descrita inicialmente em crianças japonesas e se caracteriza por rápida evolução e lesões simétricas no tronco encefálico, cerebelo e especialmente nos tálamos. Avaliamos uma menina de 7 meses de idade, que apresentou dois episódios de depressão da consciência de rápida instalação e paresias, sem alterações metabólicas. Houve uma rápida melhora na primeira crise, porém o segundo episódio foi fulminante, tendo evoluído para estado de morte encefálica em dois dias. Os estudos de ressonância magnética mostraram lesões simétricas nos tálamos e acometimento também do tronco encefálico e cerebelo. Acute necrotizing encephalopathy was initially reported in Japanese children. The rapid evolution and symmetrical brain lesions seen in the brainstem, cerebellum and specially in the thalamus characterize the disease. We studied a 7-month-old-girl, who presented with two episodes of rapid loss of consciousness and paresis without metabolic disturbances. At the first time she had a rapid improvement, but at the second episode the course was fulminant and in two days she lapsed into a clinical state of brain death. The magnetic resonance studies showed symmetrical lesions in the thalamus and additional lesions involving the brainstem and the cerebellum.